Delayed Surgical Repair of Ventricular Septal Rupture with CABG following Acute Myocardial Infraction- A Case Report - Parvez, Sultan Sarwar; Amin, Mohammad Ruhul; Haque, Reazul; Uddin, Jalal (Cardiovascular Journal, 2022)
Ventricular septal rupture (VSR) is a rare but often life-threatening mechanical complication after acute myocardial infarction. Although surgical intervention is challenging and associated with high mortality and morbidity, but it is still now the gold standard treatment. Percutaneous device closure of VSR is an option in selected patients with suitable anatomy and when surgery is contraindicated. Optimally medically managed patients who survive at least 4 weeks before elective surgery to generate scar formation at the edges of the defect in a viable infarcted tissue have the greatest outcomes. Here we report a case of VSR following acute myocardial infarction. About 3 weeks after the occurrence of ventricular septal rupture following acute myocardial infraction, surgery was successfully performed with good outcome. Cardiovasc j 2022; 15(1): 100-105